1991
DOI: 10.1021/bi00217a015
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopy of bilirubins: band assignments and application to bilirubin/lipid complexation

Abstract: Resonance Raman spectra of bilirubins IX alpha, III alpha, and XIII alpha and mesobilirubin XIII alpha in alkaline aqueous and chloroform solutions are reported. Partial band assignments of bilirubin IX alpha are proposed. The model compounds confirm assignments of bands of the Raman spectrum of bilirubin IX alpha to each of the two different pyrromethenones. Resonance Raman spectra of mesobilirubin IV alpha, vinylneoxanthobilirubinic acid, and vinylisoneoxanthobilirubinic acid in alkaline aqueous solution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 29 publications
(24 reference statements)
2
18
0
Order By: Relevance
“…Spectroscopic studies have shown that the negatively charged propionate groups of bilirubin form ion pairs with the quaternary ammonium of sphingomyelin (38); hence, we postulate that the activation enthalpy reflects the energy required to disrupt this carboxylate/quaternary ammonium ion interaction (since phosphatidylcholine and sphingomyelin possess an identical head group). In contrast to long-chain fatty acids (32), unconjugated bilirubin traverses hepatocyte plasma membranes at a rate similar to that for phosphatidylcholine vesicles.…”
Section: Discussionmentioning
confidence: 89%
“…Spectroscopic studies have shown that the negatively charged propionate groups of bilirubin form ion pairs with the quaternary ammonium of sphingomyelin (38); hence, we postulate that the activation enthalpy reflects the energy required to disrupt this carboxylate/quaternary ammonium ion interaction (since phosphatidylcholine and sphingomyelin possess an identical head group). In contrast to long-chain fatty acids (32), unconjugated bilirubin traverses hepatocyte plasma membranes at a rate similar to that for phosphatidylcholine vesicles.…”
Section: Discussionmentioning
confidence: 89%
“…Infrared microspectroscopy is increasingly used to examine the local structure of bilirubin in gallstones [l-3], both as a clinical diagnostic and as a probe of the mechanism of gallstone formation. Resonance Raman microspectroscopy has also been proposed as a diagnostic for bilirubin gallstones [4, 51. Resonance Raman spectroscopy has been used to study changes in intramolecular hydrogen bonding in the bilirubin-albumin complex [6] and in bilirubin phospholipid complexes [7]. Even surface-enhanced Raman spectroscopy has been applied to the bilirubin-albumin complex system [8].…”
mentioning
confidence: 99%
“…11,22,23 On the other hand, two intense bands at 1617 and 1584 cm 2 1 have very similar positions to those of the lactam D and lactam A ring vibrations (C5C and C5O stretches) of bilirubin, an important heme metabolite. 37 The present experiments do not permit us to quantify the production of putative degradation products or discuss their clearance rates. They also do not permit us to assess the contributions of such species to dose-limiting toxicity effects.…”
Section: Resultsmentioning
confidence: 86%